(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: A stroke is a serious life-threatening medical condition that occurs when the blood supply to part of the brain is disrupted. Spasticity is a state, in which, there is an increase in muscle tone or stiffness, which might be associated with movement and speech disorders. Spasticity is usually caused by damage to nerve pathways within the brain or spinal cord that control muscle movement. The H-reflex is a compound electromyographic (EMG) response composed of group Ia (and large group II) afferents from muscle spindles (and Golgi tendon organs) that project monosynaptically (and to a lesser extent di- and tri-synaptically) to spinal efferent ?-motoneurons (?MN), which in turn activate the muscle after an electrical current is applied to the nerve. Objective: To assess the Medical Research Council (MRC) scale in post stroke spasticity patients and to estimate the neurophysiological changes in those patients regarding H-reflex and Hmax/Mmax ratio. Methods:A randomized clinical trial involves 50 patients with stroke of both sexes. Their age ranged from (30-60 years old) suffering from upper and lower limb spasticity. They were assessed by the MRC scale to determine the grade of power of muscle. The neurophysiological test is done by using the H-reflex for both upper and lower limbs (flexor carpi radialis and soleus muscles, respectively). The maximum amplitude was measured from the peak of the first positive deflection to the peak of the negative one. The latency and the Hmax/Mmax ratio were also measured. Results: The result of this study showed a significant decrease in MRC in spastic patients (P value ?0.001). H-reflex latency in lower limbs was significantly decreased from (30.3±2.4 ms) in the normal population to (18.5±1.3) in the spastic patient. The H reflex amplitude in the lower limb was significantly increased in post stroke spasticity patients (P value ?0.05). In the upper limbs H-reflex latency in flexor carpi radialis was also significantly decreased. Regarding H reflex amplitude of the upper limb in the spastic patient was significantly increased. There is a noticeable increase in the H/M ratio in post stroke spasticity patient which was (0.51±0.92) with a significant P value of 0.005. Conclusion: Patient with post stroke spasticity had decreased in MRC scale, while H-reflex has decreased in latency and increased in amplitude, as well as decreases in Hmax/Mmax Ratio in both upper and lower limbs. Keywords: Post stroke spasticity, H-reflex latency, H-reflex amplitude, H/M ratio, MRC scale. Citation: Fawzi SM, Hamdan FB, Al-Gawwam GA, Jaafar IF. Neurophysiological changes in post stroke spasticity patients. Iraqi JMS. 2023; 21(2): 254-259. doi: 10.22578/IJMS.21.2.13